Does the construction of an ecological civilization promote firm technology investment? a Quasi-natural experiment - Chen, Meijin; Chen, Yulei; Jiang, Chengxin; Ran, Maosheng (Frontiers in Environmental Science, 2022)
The government of China has launched an environmental campaign called "Ecological Civilization Construction" and successively set up demonstration zones for ecological civilization construction in some regions since 2012. This paper studies how demonstration zones influence technology investment of local enterprises. In order to eliminate potential endogeneity issues and differences in time trends of technology investment in regions and industries outside of policy impacts, so as to accurately identify policy effects of demonstration zones, we adopted the difference-in-difference (DID) and difference-in-difference-in-difference (DDD) model. The results are as follows: first, after the policy, firms in the demonstration zones make more investment in technology, and the necessary condition for this effect is that the firms are in a state of growth. Second, the level of regional economic development has a positive moderating effect on the main results by influencing the impact of policies on local government incentives. Third, the intensity of environmental regulation expressed by air pollution index has a positive moderating effect on the main results. Fourth, firms with strong social responsibility will not be affected by such administrative pressure. Fifth, whether firms with strong financing constraints can increase technology investment depends on government subsidies.